Religious values of physicians affect their clinical practice: A meta-analysis of individual participant data from 7 countries. Issue 38 (September 2019) - Kørup, Alex Kappel; Søndergaard, Jens; Lucchetti, Giancarlo; Ramakrishnan, Parameshwaran; Baumann, Klaus; Lee, Eunmi; Frick, Eckhard; Büssing, Arndt; Alyousefi, Nada A.; Karimah, Azimatul; Schouten, Esther; Wermuth, Inga; et al.
Abstract: Background: Observational studies indicate that religious values of physicians influence clinical practice. The aim of this study was to test prior hypotheses of prevalence of this influence using a meta-analysis design. Methods: Based on a systematic literature search we performed individual participant data meta-analysis (IPDMA) on data based on 2 preselected questionnaires. Ten samples from 7 countries remained after exclusion (n = 3342). IPDMA was performed using a random-effects model with 2 summary measures: the mean value of the scale "Religiosity of Health Professionals"; and a dichotomized value of the question "My religious beliefs influence my practice of medicine." Also, a sensitivity analysis was performed using a mixed-models design controlling for confounders. Results: Mean score of religiosity (95% confidence interval [CI]) was significantly lower in the European subgroup (8.46 [6.96–9.96]) compared with the Asian samples India (10.46 [9.82–10.21]) and Indonesia (12.52 [12.19–12.84]), whereas Brazil (9.76 [9.54–9.99]) and USA (10.02 [9.82–10.21]) were placed in between. The proportion of the European physicians who agreed to the statement "My religious beliefs influence my practice of medicine" (95% CI) was 42% (26%–59%) compared with Brazil (36% [29%–43%]), USA (57% [54%–60%]), India (58% [52%–63%]), and Indonesia (91% [84%–95%]). Conclusions: Although large cross-cultural variations existed in the samples, 50% of physicians reported to be influenced by their religious beliefs. Religiosity and influence of religious beliefs were most pronounced in India, Indonesia, and a European faith-based hospital. Education regimes of current and future physicians should encompass this influence, and help physicians learn how their personal values influence their clinical practice. Abstract : Supplemental Digital Content is available in the text